Laseranwendungen in Chemie und Analytik - Herbert Stafast; J. Robert Huber (CHIMIA)
The laser is a source of “highly ordered” energy. Typical laser light properties such as monochromaticity, extreme collimation, remarkably high intensity, and temporal behavior permit unique experiments in pure and applied chemistry. The present review discusses some pertinent aspects of laser application in chemistry especially laser chemical synthesis, separation of substances and isotopic species, laser induced reactions, and laser photolytic deposition of structure. In analytical chemistry the laser has become a powerful tool opening up new techniques and improving the sensitivity, selectivity, and speed of existing methods. Application of some of these new laser methods to basic research is considered by focussing attention to one of the most exciting chemical problems, the elucidation of the microscopic pathway of a chemical reaction.